1995
DOI: 10.1002/ijc.2910600511
|View full text |Cite
|
Sign up to set email alerts
|

The role of hyaluronan in tumour neovascularization (review)

Abstract: Tumour growth and metastasis are totally dependant upon neovascularization. The target cell for tumour neovascularization is the blood-vessel endothelial cell, and specific angiogenic molecules produced or induced by the tumour are believed to initiate the process. In this report, we review one of these angiogenic molecules, the glycosaminoglycan hyaluronan (HA), which appears to have differing roles in neovascularization depending on its molecular mass. High-molecular-mass HA is anti-angiogenic whereas oligos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
204
0
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(214 citation statements)
references
References 74 publications
4
204
0
3
Order By: Relevance
“…These findings are consistent with previous observations of an anti-angiogenic effect of high molecular weight hyaluronan but an angiogenic effect of hyaluronan fragments. [45][46][47] Notably, Hyal1 in vitro requires an acidic pH for optimal activity. It is thus possible that close to neutral pH in tissues the secreted or cell surface associated Hyal1 activity 48 may induce only a limit degradation of hyaluronan, giving rise to angiogenic hyaluronan fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous observations of an anti-angiogenic effect of high molecular weight hyaluronan but an angiogenic effect of hyaluronan fragments. [45][46][47] Notably, Hyal1 in vitro requires an acidic pH for optimal activity. It is thus possible that close to neutral pH in tissues the secreted or cell surface associated Hyal1 activity 48 may induce only a limit degradation of hyaluronan, giving rise to angiogenic hyaluronan fragments.…”
Section: Discussionmentioning
confidence: 99%
“…49 Therefore, carcinoma cells that possess hyaluronidase activity may be surrounded by hyaluronan fragments that induce differentiation of endothelial cells. 47,50 The mechanism behind the tumor promoting effect of hyaluronan remains to be elucidated. It is possible that hyaluronan chains of high molecular mass, which are known to cause tissue expansion, facilitates nutrient flow in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,14 An important question is whether hyaluronidase induces endothelial cell tube formation through the formation of hyaluronan fragments with angiogenic activity or through another yet unknown mechanism. If the mechanism involves production of hyaluronan fragments, hyaluronan needs to be present in the assay.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In angiogenesis, hyaluronan plays a dual role; native high molecular weight hyaluronan prevents it, whereas hyaluronidase-degraded hyaluronan (fragments of 6 -20 saccharides) induces formation of new blood vessels in chicken chorioallantoic membrane. 5,13 We also observed that hyaluronan dodecasaccharides induced endothelial cells grown in a 3-dimensional (3D) collagen gel to form tubular structures, in a process not mediated through activation of FGF receptors. 14 These results are in conformity with those of Montesano and his colleagues, 15 who found that hyaluronan fragments acted synergistically with VEGF, but not with bFGF, in the induction of endothelial cell tube formation.…”
mentioning
confidence: 80%
See 1 more Smart Citation